Metagenomic analysis of the microbial community in kefir grains from different milk sources - JUNI SUMARMONO; RIO JATI KUSUMA; NOVIA RAHAYU; ARI SURYA SUKARNO; PUTRI DIAN WULANSARI (Society for Indonesian Biodiversity, 2023)
Abstract. Sumarmono J, Kusuma RJ, Rahayu N, Sukarno AS, Wulansari PD. 2023. Metagenomic analysis of the microbial community in kefir grains from different milk sources. Biodiversitas 24: 5302-5308. Kefir is a type of traditional fermented milk made from kefir grains. The quality of kefir grain depends on the milk medium, which impacts microbial diversity and population. This study uses metagenomic analysis to assess the microbial populations of kefir grains prepared from cow's milk and goat milk using the 16s rRNA method. The results revealed that >99% Relative Abundance (RA) of the sample's total bacteria belonged to the phylum Firmicutes and the phylum Bacteroidota, respectively. However, most of the phylum Firmicutes was found in the sample of goat milk kefir. Further investigation revealed that goat milk samples had Lactobacillus, Streptococcus, and Staphylococcus genera, while the cow milk samples contained >99% RA of Lactobacillus, Bacteroides, and Muribaculaceae. Regarding yeast, the family Saccharomycetaceae predominated in cow's milk, while goat milk had 2% of the family Saccharomycetaceae and 97% of unassigned microorganisms. The functional analysis revealed that kefir grains from the two sources had a variety of amino acid metabolisms, secondary metabolite metabolisms, and vitamin production. This metagenomic analysis shows that the type of milk affects the diversity of the population of both bacteria and yeast. This study opens up opportunities to further investigate the potential of kefir as a functional food beverage, a source of probiotics, and an antibacterial agent property.